Inhibition of mutagenic effect in winter wheat as a result of ethylmethansulfonat action - Horshchar, Vladyslav; Горщар, Владислав Іванович; Nazarenko, Mykola; Назаренко, Микола Миколайович (Дніпровський державний аграрно-економічний університет, 2022)
Chemical genetically-active substances can significantly increase the rate of mutations. The evidence of inhibition of mutagenic effect in the first generation of wheat under the action of water solution of EMS (ethylmethansulfonate) in the concentrations of 0.025%, 0.050%, 0.100% were examined in terms of germination, survival, overwintering characteristics, photosynthetic activity parameters of eight winter wheat varieties. We took into account different concentrations, the genotype of the object of mutagenic action, the ecological adaptability of a variety, the influence of the genotype-mutagenic interaction in order to find evidence of inhibition of the mutagenic effect. Therefore, the varieties Balaton and Zoloto Ukrainy are suitable for the Forest-Steppe zone, the variety Zeleny Hai was created for the droughts of the Steppe, the varieties Borovytsia, Kalancha, Nyva Odeska, Polianka, Pochaina are suitable for growing in all the zones of Ukraine. The experiments were carried out in unfavorable climatic conditions of the North Steppe (a semi-arid region with harsh winters and maximum climatic contrasts). To one degree or another, all the analyzed parameters were subjected to a clear and significant inhibiting effect by all the mutagen concentrations. Each indicator decreased in at least three gradations, sometimes there were no differences between the control and the first concentration, the first and second concentration, which depended on the genotype of the object of action. Death of some varieties after germination was observed at a rather low, not always significant, level. The death of plants in the autumn period was only typical for genotypes that are unadapted to the conditions of the region. The highest variability of the variance, due to the increase in mutagen concentrations, was seen in the indicators of germination and survival, the most genetically determined was the indicator of photosynthetic activity. There was no stimulating effect of the mutagen action, only inhibiting effects were observed. In the future, it is planned both to conduct studies of other physiological parameters of the impact of mutagenic inhibition in the first generation, and to relate the information obtained with variability, especially hereditary in subsequent generations, to monitor the genotype-mutagenic component under the action of this factor (supermutagen). Хімічні генетично-активні речовини здатні значно збільшити швидкість мутацій. Досліджено пригнічення мутагенної дії у пшениці першого покоління під дією водного розчину ЕМС (етилметансульфонат) у концентраціях 0,025 %, 0,050 %, 0,100 % за схожістю, виживаністю, характеристиками перезимівлі, фотосинтетичною активністю. Параметри восьми сортів озимої пшениці. Для виявлення доказів пригнічення мутагенної дії враховували різні концентрації, генотип об’єкта мутагенної дії, екологічну пристосованість сорту, вплив генотип-мутагенної взаємодії. Тому сорти Балатон і Золоте України придатні для зони Лісостепу, сорт Зелений гай створений для посухи Степу, сорти Боровиця, Каланча, Нива одеська, Полянка, Почайна придатні для вирощування в усіх зонах України. Досліди проводили в несприятливих кліматичних умовах Північного Степу (напівпосушливий регіон із суворими зимами та максимальними кліматичними контрастами). У тій чи іншій мірі всі аналізовані параметри зазнали явного і значного інгібуючого впливу всіх концентрацій мутагену. Кожен показник знижувався не менше ніж у трьох градаціях, інколи не було відмінностей між контролем і першою концентрацією, першою та другою концентрацією, що залежало від генотипу об’єкта дії. Загибель деяких сортів після сходів спостерігалася на досить низькому, не завжди значному рівні. Загибель рослин в осінній період характерна лише для неадаптованих до умов регіону генотипів. Найбільшу мінливість дисперсії, зумовлену підвищенням концентрації мутагену, спостерігали за показниками схожості та виживання, найбільш генетично обумовленим був показник фотосинтетичної активності. Стимулюючого ефекту мутагенної дії не спостерігалося, спостерігалися лише гальмівні ефекти. Надалі планується як проведення досліджень інших фізіологічних параметрів впливу мутагенного інгібування в першому поколінні, так і пов’язування отриманої інформації з мінливістю, особливо спадковою в наступних поколіннях, для моніторингу генотипо-мутагенного компонента в рамках дії цього фактора (супермутаген).
Пригнічення мутагенного ефекту у озимої пшениці внаслідок дії етилметансульфонату
Keywords: bread wheat; хлібна пшениця; firs generation; перше покоління; chemical mutagen; хімічний мутаген; mutation breeding; мутаційне розведення; supermutagen; супермутаген; surviving; виживаючий; concentration; концентрація; mutations; мутації; cereals; крупи; winter resistance; зимостійкість